The isolation, characterization and antifungal susceptibilities of Cryptococcus neoformans from bird excreta in Klang Valley, Malaysia - Tay, S.T.; Chai, H.C.; Na, S.L.; Hamimal, H.; Rohani, M.Y.; Soo-Hoo, T.S. (2005)
The occurrence of Cryptococcus neoformans in bird excreta in Klang valley, Malaysia was determined in this study. Of 544 samples of bird excreta collected from a local zoo, pet shops and public areas, 20 strains of C. neoformans were isolated. All C. neoformans strains were serotype A and thus identiï¬ed as C. neoformans variety grubii. All did not produce color changes on canavanineâglycineâbromothymol blue agar. All were of a-mating types, as determined by a pheromone-speciï¬c PCR assay. The antifungal susceptibility testing using agar diï¬usion method Neo-sensitabs showed that all were susceptible to amphotericin B, ï¬uconazole and itraconazole.